الجودة التربوية في الإسلام - Fadhlalla Balrammanu (Abjadia, 2016)
يتضح أن النظام التربوي الإسلامي له مجموعة من القيم الحاكمة التي تميزه عن غيره من النظم، هذه القيم تنبثق عن الرؤية الإسلامية  الشاملة، مما يعني التوافق والتناغم بينها وبين القيم العامة في المجتمع، وهذا سبب فعاليتها، والإسلام كان الرائد الأول والأعظم في وضع وبناء الأسس الصحيحة والسليمة التي تعمل على بناء مجتمع تربوي قوي، لأن المنهج الإسلامي جاء كاملاً شاملاً لكافة مجالات الحياة دون تخصيص أو تحديد، كما أنه وجود الميزان الثابت الذي يرجع إليه الإنسان بكل ما يعرض له من مشاعر وأفكار وتصورات فيزنها بهذا الميزان الثابت ليرى قربها أو بعدها من الحق والصواب، وقيمته كذلك هو للفكر التربوي مقوم منضبط بذاته، يمكن أن ينضبط به الفكر الإنساني فلا يتأرجح مع الدواخل والمؤثرات وهو ما يسمي بالتصحيح والتقويمIslam is the first religion pioneering in establishing and building the correct and healthy bases which work towards building a strong educational society. That's because the islamic methodology is complete and comprehensive for all the aspects of life without limitations and boundaries. It has also introduced the steadfast balance that any human being can refer back to whenever there is an emotional or intellectual discrepancy, so matters can be weighed in this balance to see how close or far it is from the truth. This balance as well has a self-evaluation rule in the educational process, as it will discipline thoughts and ideas so they won't be influenced by alien effects and thats what is called redirection and reevaluation.